Assessing the Potential Impact of Disruptions Due to COVID-19 on HIV Among Key and Lower-Risk Populations in the Largest Cities of Cameroon and Benin. (1st July 2021) - Silhol, Romain; Geidelberg, Lily; Mitchell, Kate M.; Mishra, Sharmistha; Dimitrov, Dobromir; Bowring, Anna; Béhanzin, Luc; Guédou, Fernand; Diabaté, Souleymane; Schwartz, Sheree; Billong, Serge C.; Njindam, Iliassou Mfochive; et al.
Abstract : Background: The COVID-19 pandemic indirectly impacts HIV epidemiology in Central/West Africa. We estimated the potential impact of COVID–19-related disruptions to HIV prevention/treatment services and sexual partnerships on HIV incidence and HIV-related deaths among key populations including female sex workers (FSW), their clients, men who have sex with men, and overall. Setting: Yaoundé (Cameroon) and Cotonou (Benin). Methods: We used mathematical models of HIV calibrated to city population–specific and risk population–specific demographic/behavioral/epidemic data. We estimated the relative change in 1-year HIV incidence and HIV-related deaths for various disruption scenarios of HIV prevention/treatment services and decreased casual/commercial partnerships, compared with a scenario without COVID-19. Results: A 50% reduction in condom use in all partnerships over 6 months would increase 1-year HIV incidence by 39%, 42%, 31%, and 23% among men who have sex with men, FSW, clients, and overall in Yaoundé, respectively, and 69%, 49%, and 23% among FSW, clients, and overall, respectively, in Cotonou. Combining a 6-month interruption of ART initiation and 50% reduction in HIV prevention/treatment use would increase HIV incidence by 50% and HIV-related deaths by 20%. This increase in HIV infections would be halved by a simultaneous 50% reduction in casual and commercial partnerships. Conclusions: Reductions in condom use after COVID-19 would increase infections among key populations disproportionately, particularly FSW in Cotonou, who need uninterrupted condom provision. Disruptions in HIV prevention/treatment services have the biggest impacts on HIV infections and deaths overall, only partially mitigated by equal reductions in casual/commercial sexual partnerships. Maintaining ART provision must be prioritized to minimize short-term excess HIV-related deaths. Abstract : Supplemental Digital Content is Available in the Text.